EVALUATION OF AQUIFER PROTECTIVE CAPACITY USING ELECTRICAL RESISTIVITY METHOD IN LAMBATA, KWALI AREA COUNCIL, ABUJA (FUDMA JOURNAL OF SCIENCES, 2022)
This study evaluated the aquifer protective capacity of Lambata in Kwali area council of Abuja, using electrical resistivity method. The obtained data were interpreted manually by partial curve matching and the obtained results were iterated using WINREIST software. The first layer is the topsoil whose resistivity range from 127.7 to 562.4 Î©m and its thickness range from 0.7 to 1.6 m. The second layer is laterite and its resistivity range from 302.3 to 937.6 Î©m, the thickness of the second layer range from 3.7 to 13.3 m. The third layer is a clay formation whose resistivity range from 46.7 to 88.8 Î©m and its thickness range from 6.6 to 27.9 m. The fourth layer is a weather/ fractured basement, this layer is the aquifer and it is confined by the overlying clay formation. Its resistivity range from 59.0 to 870.2 Î©m, while its thickness range from 6.0 to 28.5 m.  The fifth layer is the fresh basement whose resistivity range from 1038.5 to 4992.5 Î©m. The total longitudinal conductance values of the overburden in the study area range from 0.00143 to 0.410334 mÎ©-1. The average aquifer thickness in the study area is 16.60 m. The aquifer protective capacity is about 93.3% moderate and 6.7% weak. The aquifer protective capacity of the study area is fairly good but not sufficient to protect the groundwater in the area from pollution. We therefore strongly suggest that there should be proper environmental and waste monitoring management in the study area to safeguard the groundwater
Keywords: Anthropogenic, aquifer, groundwater, longitudinal conductance, protective capacity